Why don't tigers eat bananas? - Smith, Katherine, 1967- (Columbus, Ohio : Waterbird Books, 2004)
Presents information about tigers in a question and answer format, explaining how and what they eat, and discussing their physical characteristics, behaviors, and life cycle.
"First published in Great Britain in 2004 by ticktock Media, Ltd."--T.p. verso.
Includes index.
Horn Book.
School Library Journal.
3.5
K-3
Keywords: Tigers -- Miscellanea -- Juvenile literature; Questions and answers; Tigers -- Miscellanea; Questions and answers; Tigers -- Miscellanea